Modos de alfabetizar no grupo escolar Clarimundo Carneiro - 1963 A 1973 - Lepick, Vanessa (2013)
This study is inserted in the field of qualitative research in education and aims to conduct a research about the modes of literacy in the Grupo Escolar Clarimundo Carneiro, in Uberlândia, during 1963 to 1973. The questions that arise are: What were the representations of these literacy teachers about literacy? How was the process for reading and writing at school? How were implemented student evaluations? What were the instructional materials used in this process? The theoretical basis chosen is cultural history. And the methodology comes from thematic oral history and documental. Thus, from the oral history was possible to resume the experiences of literacy teachers in the classroom and their ways of teaching the Portuguese language. Furthermore, it allows valorizing the experiences of these literacy teachers and revealing details that would not be informed in official documents. For this, we interviewed four literacy teachers who have worked for at least five years in the same job position during the period studied. We also interviewed the first principal who led the school group. The documental sources participate in a complementary way to the study from analysis of materials used in school by literacy teachers. In this study we verified that the Clarimundo Carneiro School Group during their existence preserved the ideals of the earliest school groups installed in Minas Gerais. The literacy teachers followed the guidelines of the principal as to the use of prescriptions for the Programa de Língua Pátria (National Language Program). The teaching method used in literacy was the same determined by National Language Group, in other words, the Global method. And the booklet adopted was As Mais Belas Histórias of Lúcia Casasanta. However for literacy teachers who taught for repeaters or those studying in evening shift, they were allowed the use of another methodology and teaching material. The way to evaluate the students in Group was through tests and the corrections should be consistent and stringent. We also verified that the principals were influencing directly in the practices exercised in literacy classes.